Pengaruh pengawasan dan vudaya organisasi terhadap kinerja karyawan anglo eastern plantation group (UKINDO BLANKAHAN) - oktavia sabrina br karo oktavia (Akuntansi Prima, 2021)
Supervision is an activity in the company to achieve company goals. Supervision is needed to improve the quality of work of human resources to advance the company. In addition to Supervision, Organizational Culture can also affect the personal lives of employees and affect the progress of the company. Therefore a company needs to form a good organizational culture. The objective of the study is to test and analyze the effect of supervision and organizational culture on employee performance at the Anglo Eastern Plantation Group (Ukindo Blankahan). The research used a quantitative research method. This type of research is quantitative descriptive and the nature of this study is an eplanatory research. The research data were analyzed by using multiple linear regression analysis. The research populaions were 221 employees with the samples of 143 respondents. The result of the study showed that the T test on supervision was T-count 2.222> T-table 1.6558 with a significant level of 0.000 <0.05. Therefore, it is concluded that partially supervision has a positive and significant effect on employee performance at Anglo Eastern Plantation Group (Ukindo Blankahan). Partially, on organizational culture, it was found that T- count> T-table or (12,173> 1.6558) with a significant level of 0.000 <0.05. Therefore, it was concluded that partially, organizational culture has a positive and significant effect on employee performance at Anglo Eastern Plantation Group (Ukindo Blankahan). The result of the study shows that supervision and organizational culture have a significant effect on employee performance at Anglo Eastern Plantation Group (Ukindo Blankahan) in which F-count 86.44> F-table 3.07 with a significant value of 0.004 <0.05 which means that Ho is rejected and Ha is accepted at a level of significance 0.004 <0.05.